2007
DOI: 10.1073/pnas.0704116104
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and proofreading both contribute significantly to the fidelity of RNA polymerase III transcription

Abstract: We examine here the mechanisms ensuring the fidelity of RNA synthesis by RNA polymerase III (Pol III). Misincorporation could only be observed by using variants of Pol III deficient in the intrinsic RNA cleavage activity. Determination of relative rates of the reactions producing correct and erroneous transcripts at a specific position on a tRNA gene, combined with computational methods, demonstrated that Pol III has a highly efficient proofreading activity increasing its transcriptional fidelity by a factor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…5B, lane 1). Shorter products appeared to result from misincorporation of UTP in place of CTP, as they did not appear when UTP was absent (forming the 13-mer instead, lane 9) or when the 16-mer was formed by the sequential addition of CTP and UTP (data not shown; note that the addition to misincorporated nucleotides is extremely slow (27)). Curiously, while optimizing the conditions for forming the 16-mer RNA-containing elongation complex (by varying the proportions of the two DNA strands and RNA; compare lane 1 with lanes 2-4), we observed that formation of the 16-mer-RNA elongation complex required the assembly of the non-transcribed DNA strand (although some extension to nt 12 did occur in its absence; data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5B, lane 1). Shorter products appeared to result from misincorporation of UTP in place of CTP, as they did not appear when UTP was absent (forming the 13-mer instead, lane 9) or when the 16-mer was formed by the sequential addition of CTP and UTP (data not shown; note that the addition to misincorporated nucleotides is extremely slow (27)). Curiously, while optimizing the conditions for forming the 16-mer RNA-containing elongation complex (by varying the proportions of the two DNA strands and RNA; compare lane 1 with lanes 2-4), we observed that formation of the 16-mer-RNA elongation complex required the assembly of the non-transcribed DNA strand (although some extension to nt 12 did occur in its absence; data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…1B, lane 1. That their size heterogeneity resulted from slippage was confirmed by walking the entire cluster of bands upon the addition of UTP (lane 2) or UTPϩATP (lane 3; note that most of the complexes in lane 3 extended to C27 instead of A26 due to misincorporation of UMP and the lack of proofreading by pol III⌬ (27) and that ϳ20% of complexes did not chase).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One could be initially surprised to find TFIIS associated with class III genes, since Pol III has an intrinsic transcript cleavage activity that depends on Rpc11 subunit (Chedin et al 1998;Alic et al 2007). Rpc11 has a C-terminal Zn loop that bears an RSADE motif, critical for transcript cleavage, that closely resembles the C-terminal domain of TFIIS (Chedin et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, repetition of our cleavage assay with a scaffold that contains only a single mismatch at the RNA 3 0 end, mimicking the situation after a misincorporation event, induced efficient RNA cleavage (not shown). For Pol III, the intrinsic cleavage activity was recently shown to enable proofreading in a manner dependent on the A12.2 homolog C11 (Alic et al, 2007), which is required for the intrinsic cleavage activity of Pol III (Chedin et al, 1998;Landrieux et al, 2006).…”
Section: Possible Functions Of the Cleavage Activitymentioning
confidence: 99%